Peran Kontrol Diri dalam Memoderatori Pengaruh Electronic Word of Mouth (E-WOM) terhadap Shopaholic Generasi Z Kabupaten Malang - Zuhroh, Luthfiatus; ‘Izzah, Nida Mukhlishotul; Khusna, Mafrukhatul (Flourishing Journal, 2025)
Shopaholic has become a serious issue in the digital era, characterized by shopping habits that exceed basic needs. This study examines the influence of Electronic Word of Mouth (E-WOM) and self-control on shopaholic tendencies among Generation Z in Malang. This study used a correlational quantitative approach with a sample of 270 respondents from a total population of 386,976, selected through purposive sampling, and data collected via questionnaire. Multiple regression analysis showed a significance value of E-WOM of 0.48 (not significant) while self-control was very significant with a value of 0.00. The results of the F-test (p < 0.000) confirmed the combined effect of E-WOM and self-control on shopaholic behavior. The findings indicate that strong self-control reduces shopaholic behavior, while the impact of E-WOM is not significant. This study explains that good individual self-control can reduce the influence of Electronic Word of Mouth (E-WOM) on shopaholic tendencies. Self-control in individuals will enable them to rationally control their thought patterns and control their behavior to avoid engaging in consumptive behavior due to exposure to social media content. This study emphasizes that increasing self-control is important to suppress excessive shopping habits among the younger generation. AbstrakShopaholic menjadi isu serius di era digital, ditandai oleh kebiasaan belanja yang melampaui kebutuhan utama. Penelitian ini memeriksa peran kontrol diri dalam memoderatori pengaruh Electronic Word of Mouth (E-WOM) terhadap shopaholic generasi Z di Kabupaten Malang. Penelitian ini menggunakan pendekatan kuantitatif moderasi dengan sampel sebanyak 270 responden dari total populasi 386.976, dipilih melalui purposive sampling, dan data dikumpulkan via kuesioner. Analisis Moderated Regression Analysis (MRA) menunjukkan nilai signifikansi E WOM sebesar 0,48 (tidak signifikan) sedangkan kontrol diri sangat signifikan dengan nilai 0,00. Hasil uji F (signifikansi 0,000) mengonfirmasi adanya efek gabungan E WOM dan kontrol diri terhadap perilaku shopaholic. Temuan penelitian ini menunjukkan bahwa tingkat kontrol diri yang tinggi akan mampu menurunkan pengaruh E-WOM terhadap shopaholic. Kontrol diri pada individu akan membuat individu mampu mengendalikan pola pikir secara rasional dan pengendalian perilaku untuk tidak melakukan perilaku konsumtif akibat paparan konten media sosial. Penelitian ini menekankan bahwa peningkatan kontrol diri penting untuk menekan kebiasaan belanja berlebihan di kalangan generasi muda.